PERANCANGAN DAN PEMBUATAN APLIKASI PERHITUNGAN HPP (HARGA POKOK PRODUKSI) PERCETAKAN MELIWIS SURABAYA DENGAN MENGGUNAKAN METODE JOB ORDER COSTING - Hendra, Tommy; Dewi, Lily Puspa; Budhi, Gregorius Satia (Jurnal Infra, 2014)
Design and manufacture the application calculations of cost of goods production at Surabaya Meliwis printing company using job order costing are: elimination.Meliwis printing is a company engaged in the field of offset printing. The company will produce when if taking orders from the customer. At this time all processes in the company are still done manually, although in the determination of the sale price is still relying on salesmen to sales data. It is a big risk for the company, especially in terms of determining cost of goods production to determine the selling price to the customer.Based on the problems, there is a need yo designing the application calculations of HPP (cost of goods production) to determine the sale price thats clear and obvious administrative system. The development process uses Visual Basic .NET and My SQL Server 2005.Company application has been in accordance with the needs of the store. This application can be assisted the owner in knowing the finance company stores through reports which is generated by this application. The results obtained from the questionnarre pressents 60% of users believe an application has been beneficial to both the company and 40% of users believe an application has been extremely beneficial to both